Vortioxetine Treatment Reverses Subchronic PCP Treatment-Induced Cognitive Impairments: A Potential Role for Serotonin Receptor-Mediated Regulation of GABA Neurotransmission - Pehrson, Alan L.; Pedersen, Christian S.; Tølbøl, Kirstine Sloth; Sanchez, Connie (Frontiers in Pharmacology, 2018)
Major depressive disorder (MDD) is associated with cognitive impairments that may contribute to poor functional outcomes. Clinical data suggests that the multimodal antidepressant vortioxetine attenuates some cognitive impairments in MDD patients, but the mechanistic basis for these improvements is unclear. One theory suggests that vortioxetine improves cognition by suppressing γ-amino butyric acid (GABA)ergic neurotransmission, thereby increasing glutamatergic activation. Vortioxetine’s effects on cognition, GABA and glutamate neurotransmission have been supported in separate experiments, but no empirical work has directly connected vortioxetine’s cognitive effects to those on GABA and glutamate neurotransmission. In this paper, we attempt to bridge this gap by evaluating vortioxetine’s effects in the subchronic PCP (subPCP) model, which induces impaired cognitive function and altered GABA and glutamate neurotransmission. We demonstrate that acute or subchronic vortioxetine treatment attenuated subPCP-induced deficits in attentional set shifting (AST) performance, and that the selective 5-HT3 receptor antagonist ondansetron or the 5-HT reuptake inhibitor escitalopram could mimic this effect. Furthermore, acute vortioxetine treatment reversed subPCP-induced object recognition deficits in rats, while subchronic vortioxetine reversed subPCP-induced object recognition and object placement impairments in mice. Finally, subPCP treatment reduced GABAB receptor expression in a manner that was insensitive to vortioxetine treatment, and subchronic vortioxetine treatment alone, but not in combination with subPCP, significantly increased GABA’s affinity for the GABAA receptor. These data suggest that vortioxetine reverses cognitive impairments in a model associated with altered GABA and glutamate neurotransmission, further supporting the hypothesis that vortioxetine’s GABAergic and glutamatergic effects are relevant for cognitive function.